2019
DOI: 10.2478/gsr-2019-0005
|View full text |Cite
|
Sign up to set email alerts
|

Effect of macromolecular mass transport in microgravity protein crystallization

Abstract: To investigate the effect of macromolecular transport and the incorporation of protein aggregate impurities in growing crystals, experiments were performed on the International Space Station (ISS) and compared with control experiments performed in a 1G laboratory environment. Crystal growth experiments for hen egg-white lysozyme (HEWL) and Plasmodium falciparum glutathione S-transferase (PfGST) were monitored using the ISS Light Microscopy Module (LMM). Experiments were performed applying the liquid–liquid cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 35 publications
1
8
0
Order By: Relevance
“…The reduction in growth rate under microgravity versus unit gravity can be explained by the driving force ratio of diffusion as defined by Tanaka et al 47 , 48 . Data from SPX10 as well as previous studies demonstrated differences in the growth rate and geometry of crystals grown in microgravity versus unit gravity control experiments 44 , 45 , 49 . However, for the crystals under investigation, as mentioned previously, changes were not observed for shape and geometry for microgravity versus unit gravity crystals.…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…The reduction in growth rate under microgravity versus unit gravity can be explained by the driving force ratio of diffusion as defined by Tanaka et al 47 , 48 . Data from SPX10 as well as previous studies demonstrated differences in the growth rate and geometry of crystals grown in microgravity versus unit gravity control experiments 44 , 45 , 49 . However, for the crystals under investigation, as mentioned previously, changes were not observed for shape and geometry for microgravity versus unit gravity crystals.…”
Section: Discussionmentioning
confidence: 60%
“…Our investigations addressed two prevailing theories regarding why microgravity-grown protein crystals often exhibit improved X-ray diffraction statistics compared to unit gravity control crystals. The first theory concerning differences in crystal growth rates found in our experiments was previously addressed 44 , 45 . The reduction in growth rate under microgravity versus unit gravity can be explained by the driving force ratio of diffusion as defined by Tanaka et al 47 , 48 .…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Consequently, it is not surprising that crystallization in space has received much financial support from both public space agencies and private companies until the last decade [1]. Since the early protein crystallization space adventure in 1984, many instruments have been tested under microgravity conditions [2][3][4][5][6][7]. At first, the results were not very conclusive, but interest did not decline, leading to a vast amount of research into reduced gravity environments [2][3][4][5][6][7], most of which reported crystal quality enhancements and strongly contributed to a better understanding of the nucleation and growth of protein crystals [4,[8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Since the early protein crystallization space adventure in 1984, many instruments have been tested under microgravity conditions [2][3][4][5][6][7]. At first, the results were not very conclusive, but interest did not decline, leading to a vast amount of research into reduced gravity environments [2][3][4][5][6][7], most of which reported crystal quality enhancements and strongly contributed to a better understanding of the nucleation and growth of protein crystals [4,[8][9][10]. Although several parameters, such as the isoelectric point and water content, were not considered when analyzing the results, the observed improvement in crystal quality was explained on the basis of reduced crystal sedimentation, density-driven convection flows provoking the formation of depletion zones around growing crystals [11][12][13][14], and the reduced incorporation of impurities [4,15,16].…”
Section: Introductionmentioning
confidence: 99%